2013
DOI: 10.1111/avsc.12030
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fire regeneration inMediterranean reforested sites as affected by mechanical site preparation: lessons for restoration

Abstract: Question The importance of silvicultural site preparation techniques in determining vegetation succession is increasingly recognized. We studied the effects of mechanical site preparation (MSP) on post‐fire vegetation regeneration within reforested sites in Mediterranean Israel. Location Upper Galilee region, Israel. Methods Vegetation cover and composition, ruderal species colonization and pine regeneration were monitored in four reforested sites for 3 yr following wildland fires that burned mature Pinus brut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Management decisions in favor of recruiting pine plantations, however, may lead to the disruption in the natural recovery process in such forests (Maestre & Cortina 2004, Gómez-Aparicio et al 2009). On the contrary, it is reported that plowing has minor and temporary effects on plant species richness and vegetation cover; however, it negatively affects pine regeneration in Mediterranean pine woodlands (Hibsher et al 2013). As the benefits of planting seedlings offset by its negative effect on the small mammal community in a pine woodland dominated by the non-serotinous species Pinus nigra, it has been suggested that a multi-criteria approach should be implemented before selecting post-fire management practices in such forests (Espelta et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Management decisions in favor of recruiting pine plantations, however, may lead to the disruption in the natural recovery process in such forests (Maestre & Cortina 2004, Gómez-Aparicio et al 2009). On the contrary, it is reported that plowing has minor and temporary effects on plant species richness and vegetation cover; however, it negatively affects pine regeneration in Mediterranean pine woodlands (Hibsher et al 2013). As the benefits of planting seedlings offset by its negative effect on the small mammal community in a pine woodland dominated by the non-serotinous species Pinus nigra, it has been suggested that a multi-criteria approach should be implemented before selecting post-fire management practices in such forests (Espelta et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Particularly crucial is the capacity of young recruits to survive the long and dry hot season during the first few years following emergence (Hibsher et al. ; Osem et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, ; Hibsher et al. ) in the understorey of the pine plantations, the opportunity for converting these simply structured monocultures into mixed broad‐leaved–conifer woodlands is being seriously considered (Osem et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However for those variables that did not meet the assumptions of normality of residuals and homogeneity of variance, log‐transformed or rank‐transformed data were used (Conover & Iman ; Hibsher et al. ). The Tukey–Kramer HSD test was used for post‐hoc comparisons.…”
Section: Methodsmentioning
confidence: 99%